Industrial Possibilities of Idjen Crater Lake Water - Tjiook Tiauw Kien (Journal of Mathematical and Fundamental Sciences, 1967)
Abstract. Idjen Crater Lake Water containing 600.000 tons of sulfur 1) 4) (compare total Indonesian sulfur reserves of 1 million tons 2) has been investigated as to the possibility of its use as an industrial raw material. Although sulfate can most conveniently be recovered from the dilute acid solution as gypsum, it is advantageously suggested to convert the latter into ammonium sulfate, thus potentially increasing the possibility of fertilizer production in Indonesia. A flowsheet has been proposed. Although processing the Lake Water seems to be feasible front a technological point of view, a possible danger of Idjen Volcano eruption, however small, should not be overlooked.  Ichtisar. Air Kawah Idjen jang mengandung 600.000 ton belerang (bandingkan dengan tjadangan Indonesia sebanjak sedjuta ton) telah diselidiki mengenai kemungkinan untuk dipakainja sebagai bahan mentah industri. Meskipun sulfatnja dengan mudah dapat diperoleh dari larutan asam jang entjer itu sebagai gips, telah diusulkan untuk mengolah terus zat achir ini mendjadi ammoniumsulfat (Z.A.), jang merupakan bahan pupuk jang berharga. Walaupun pengolahan Air Kawah Idjen ternjata mungkin sekali dari sudut teknologi, perlu diselidiki pula kemungkinan meletusnja gunung api tsb., meskipun hal itu telah lama tidak terdjadi.